Stabilization and DOB-Based Disturbance Rejection for MBT Gun-BarrelElevation Drive - (:unkn) unknown (My University, 2020)
Control systems for main battle tanks become more important while the vehicles become more complex. Mobile vehicles inbattlefield lead to the requirement of firing during the motion instead of pausing each time the main battle tank engages a target.This demand can be achieved by weapon control system that minimize the tank hull movement effects on the barrel. Systemsdesigned for this stabilization task are basically closed loop servo systems that control the angular position of the barrel byusing feedback signals produced by a rate gyroscope mounted on the barrel (breech) to measure its angular velocity. Secondgenerationcontrol systems contain an extra gyro which feeds the tanks movement forward in the system to make the turretmore sensitive and rapid against the disturbance due to tanks movement. In this paper we use a disturbance observer that donot require measurements of muzzle angular velocity and rough terrain caused disturbance due to tank movement. Designedobserver eliminate the requirement for measurements of near-perfect feedforward signal.

Savaş tanklarındaki son yıllardaki gelişmeler kullanılan kontrol sistemlerini daha önemli hale getirmiştir. Bu araçların savaş alanında hareket halinde olması, bir hedefe ateş etme sırasında durmak yerine hareket esnasında ateş etmelerini gerekli kılmaktadır. Bu gereklilik, tank gövdesi hareketlerinin namluya olan etkisini minimize eden silah kontrol sistemi ile sağlanabilir. Bu stabilizasyon işlevi için namlu üzerine monte edilen jiroskoptan alınan açısal konumun geri beslemesiyle çalışan kapalı-evrim servo kontrol sistemleri kullanılır. İkinci nesil kontrol sistemlerinde, tank gövdesinin hareketi nedeniyle oluşan bozucu etkilere karşıtareti daha hassas ve hızlı kılan, ileri beslemeli kontrol için ekstra bir jiroskop daha kullanıl ır. Bu makalede ise tankın hareketi nedeniyle oluşan bozucu etkilerin ölçülmesi ihtiyacını ortadan tamamen kaldıran bir ‘bozucu etki gözleyicisi’ kullanılmaktadır. Tasarlanan gözleyici sayesinde bozucu etkinin hatasız olarak ölçülmesi ve ileri besleme kontrol ile elimine edilmeye çalışılması gerekliliği ortadan kalkmaktadır.
Savaş Tankı Namlu Yükseliş Açısı Tahrik Sistemi Stabilizasyonu ve DOB-Temelli Bozucu Dışlama